Pengaruh E-Service Quality dan Promosi Penjualan terhadap Minat Menggunakan Dompet Digital LinkAja pada Followers Instagram @linkaja - Alfina Agustin; Danang Kusnanto (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to examine and analyze the effect of e-service quality and sales promotion on interest in using LinkAja digital wallets. The primary data in this study were data obtained from distributing questionnaires to LinkAja users and Instagram followers @linkaja with 348 samples using a non-probability sampling method with incidental sampling. The analysis technique used is scale range analysis and path analysis with the help of Internal Successive Method (MSI), Microsoft Excel program, and SPSS application. The results of this study indicate descriptively that the e-service quality, sales promotion, and interest in using digital wallets are in the very good category. Based on the results of the verification analysis, the e- service quality and sales promotion variables influence each other and show a very strong level of influence. The partial effect obtained from the e-service quality and sales promotion on interest in using digital wallets are 42.8% and 27%, respectively, with a total simultaneous effect of 69.8%. while the remaining 30.2% is influenced by other variables not examined.